2014
DOI: 10.3345/kjp.2014.57.7.297
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive understanding of atrial septal defects by imaging studies for successful transcatheter closure

Abstract: Transcatheter closure of atrial septal defects has become a popular procedure. The availability of a preprocedural imaging study is crucial for a safe and successful closure. Both the anatomy and morphology of the defect should be precisely evaluated before the procedure. Three-dimensional (3D) echocardiography and cardiac computed tomography are helpful for understanding the morphology of a defect, which is important because different defect morphologies could variously impact the results. During the procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The current study showed a significant association between primum ASD type with each of large ASD with posteroinferior deficient rims, large ASD diameter, and large IAS. This finding is in agreement with the results of the Song study in South Korea (30), which stated that on echocardiography, the primum ASD is characterized by large ASD with deficient rims and large IAS. The mean ASD diameter was 19.7 mm.…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed a significant association between primum ASD type with each of large ASD with posteroinferior deficient rims, large ASD diameter, and large IAS. This finding is in agreement with the results of the Song study in South Korea (30), which stated that on echocardiography, the primum ASD is characterized by large ASD with deficient rims and large IAS. The mean ASD diameter was 19.7 mm.…”
Section: Discussionsupporting
confidence: 93%